ASPEK MEGALITIK SITUS SEWO, SOPPENG - Citra Andari (WalennaE, 2001)
Megalithic tradition in Indonesia based on archaeological evidences emerged after agricultural skill began to spread and it reached its time in metal age. At Sewo sites, Soppeng, megalithic remains are divided into two classifications: living monument tradition and dead monument tradition. Living monument tradition includes stone veneration, stone altars, and dolmen. While dead monument tradition includes pil marked stone, stone mortar and stone for holy water. Nowadays, periodical agricultural ceremonies (mappassili) are still using living monument tradition. Ceremonies tradition with the tendency of megalithic continuance at Sewo sites are based on social situations, strong emotional bounds with prehistoric conception and geographical isolation from religion concept, especially Islam.